The Curriculum of the educable mentally retarded at three different levels - Garcia, Remedios Gabatin 1928- (s.n.], 1967)
This paper investigates the curriculum of the educable mentally retarded at three different levels. This includes how the curriculum is planned for the educable mentally retarded children, the bases in planning or organizing the curriculum of the mentally retarded children, and the curricular activities that are offered to these educable mentally retarded children in each developmental level.